Angiotensin II type 1a receptor signalling directly contributes to the increased arrhythmogenicity in cardiac hypertrophy. (December 2013) - Yasuno, Shinji; Kuwahara, Koichiro; Kinoshita, Hideyuki; Yamada, Chinatsu; Nakagawa, Yasuaki; Usami, Satoru; Kuwabara, Yoshihiro; Ueshima, Kenji; Harada, Masaki; Nishikimi, Toshio; Nakao, Kazuwa
<x xml:space="preserve">Abstract</x> Background and Purpose Angiotensin II has been implicated in the development of various cardiovascular ailments, including cardiac hypertrophy and heart failure. The fact that inhibiting its signalling reduced the incidences of both sudden cardiac death and heart failure in several large‐scale clinical trials suggests that angiotensin II is involved in increased cardiac arrhythmogenicity during the development of heart failure. However, because angiotensin II also promotes structural remodelling, including cardiomyocyte hypertrophy and cardiac fibrosis, it has been difficult to assess its direct contribution to cardiac arrhythmogenicity independently of the structural effects. Experimental Approach We induced cardiac hypertrophy in wild‐type (WT) and angiotensin II type 1a receptor knockout (AT1aR‐KO) mice by transverse aortic constriction (TAC). The susceptibility to ventricular tachycardia (VT) assessed in an in vivo electrophysiological study was compared in the two genotypes. The effect of acute pharmacological blockade of AT1R on the incidences of arrhythmias was also assessed. Key Results As described previously, WT and AT1aR‐KO mice with TAC developed cardiac hypertrophy to the same degree, but the incidence of VT was much lower in the latter. Moreover, although TAC induced an increase in tyrosine phosphorylation of connexin 43, a critical component of gap junctional channels, and a reduction in ventricular levels of connexin 43 protein in both genotypes, the effect was significantly ameliorated in AT1aR‐KO mice. Acute pharmacological blockade of AT1R also reduced the incidence of arrhythmias. Conclusions and Implications Our findings demonstrate that AT1aR‐mediated signalling makes a direct contribution to the increase in arrhythmogenicity in hypertrophied hearts independently of structural remodelling.